Thermal and mechanical properties of Ta2O5 doped La2Ce2O7 thermal barrier coatings prepared by atmospheric plasma spraying - Zhang, Hao; Sun, Junbin; Duo, Shuwang; Zhou, Xin; Yuan, Jieyan; Dong, Shujuan; Yang, Xiong; Zeng, Jinyan; Jiang, Jianing; Deng, Longhui; Cao, Xueqiang (Journal of the European Ceramic Society, 2019)
La2Ce2O7 (LC) is a new promising thermal barrier coating (TBC) material for high-temperature applications. However, the sudden decrease of thermal expansion coefficient (TEC) at ∼623 K limits its application. In this study, the plasma-sprayed La2Ce1.7Ta0.3O7.15 (LCT) coating was developed by partial substitution of Ce4+ in LC with Ta5+. LCT coating shows lower thermal conductivity between 298 K and 1273 K (0.54–0.71 W/(m·K)) than LC coating (0.65–0.85 W/(m·K)) and the traditional yttria partially stabilized zirconia (YSZ) coating (1.53–1.72 W/(m·K)). It also exhibits excellent thermal stability at least up to 1573 K for 1000 h. What is more, the sudden TEC drop is suppressed owing to the reduced oxygen vacancy concentration governed by Ta5+-substitution content. As a result, LCT TBC shows an improved thermal cycling lifetime in an air furnace as compared to LC TBC.